Manajemen Kebidanan Pada Ny. J Dengan Abortus Inkomplit - Eka Sri Purwandari; Alfina Indah Susanti (STIKES dan AKZI Karya Husada Kediri, 2023)
Incomplete abortion is one of the contributors to abortion cases that occur in mothers. Inappropriate management can worsen the mother's condition and can even cause death. The purpose of this study was to provide midwifery care for pregnant women with incomplete abortions through a comprehensive Varney midwifery care management mindset approach. The method used is a case study to explore the problem. The research subject is Mrs. J 20 years old G1P0A0 12 weeks gestation which was carried out in May 2022, in the delivery room of Amelia Hospital. Data collection techniques include primary data including physical examination, interviews, observation and secondary data, including documentation studies and literature studies. Data analysis was carried out by creating narratives from the results of interviews and examinations using Varney's 7 steps. From the case study conducted on Mrs. J The diagnosis of incomplete abortion was made based on the history and physical examination. Mrs. J came with the main complaint of bleeding from the birth canal since three days ago, on May 15, 2022, to be precise. Consciousness composmentis, blood pressure 90/60 mmHg, pain, vaginal discharge of blood, examination in the fingertips felt tissue. Ultrasound examination with impression of residual tissue. This patient was treated in the form of curettage. At two hours post curettage the mother's condition was getting better and no obstacles were found during the implementation of the action. Patients are observed and given care according to the authority of midwives at the hospital which prioritizes collaborative and independent care. Appropriate management in accordance with the conditions and needs of the mother supports the improvement of the physical and psychological condition of the mother in dealing with her case